Professional mobility: philosophical and sociological aspect - Sushentseva, Liliya; Havrylyuk, Marianna (Lviv Politechnic Publishing House, 2016)
In the article the problem of competitiveness of able-bodied citizens and their capacity for professional mobility have been studied. The professional mobility has been researched by foreign and Ukrainian scientists. The European scientists started empirical investigation of the mobility processes in the mid-XXth century. It has been found that the division of labor in the history of human society led to the emergence of professions and was the main (motivation) driving force of human progress. Due to it people started to differ from one another. Considering this fact, P. Kropotkin emphasized the future professionals’ need for the development of mobility. The basis for the study of such phenomenon as professional mobility is the research works of E. Durkheim and M. Weber. Functional approach to the analysis of professional mobility as a social phenomenon became the fundamental base of their research. Philosophers interpret the concept of “mobility” in terms of dialectic Law of the Development of Society, and sociologists distinguish the dynamism of social development as the main factor that determines the nature and the content of social and professional mobility. It has been proved that among the able-bodied citizens who deliberately have chosen a certain profession and have mastered it, there are people who are forced to get training for a new occupation and pursue a different profession. The research results let us state that among these people there will be those who will not always be ready for professional mobility. Professional mobility has been described as a condition and a consequence of the professional division of labour according to the society needs by changing the profession or training for a new one and has been also considered as a change of employment position or role of the worker that is caused by the change of the place of work or profession.
Keywords: social mobility; professional mobility; profession